Some reflections on the relationship between work and education - Ostrovski, Crizieli Silveira; Raitz, Tânia Regina (Acta Scientiarum. Education, 2017)
This is a theoretical essay aimed at discussing the concept of work and its relationship with education since both are activities specific of man. For this purpose, it is based on Marx’s assumptions (1982), and Marx and Engels (1996) that present work as a human natural need when accomplishing the material exchange between man and nature. And this is what differentiates the human beings from the animals, with the ability to create and to recreate, projecting his/her existence that occurs by the conscious action of work. In developing the theme, we focused on the conception of work as educational principle, as a value of creator and maintainer use, as promoter of satisfactions of human needs. The article has theoretical foundations in authors such as Marx (1982), Marx and Engels (1996), Saviani, (2006, 2007, 2009), Frigotto (2001a, 2001b, 2010, 2011), among others. The theme will be historically contextualized according to the organization of society, work and education. The approach takes into account the man as a historical being and the work as an educational principle, consisting of a fundamental theme that does not end in the epistemological, social and educational contexts.